The Effect Of Nano Technology Liquid Organic Fertilizer On The Growth Of Spinach (Amaranthus hybridus l.) Cultivated Hydroponically - Yurico Utami; Resti Fevria; Vauzia Vauzia; Irma Leilani Eka Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Hydroponic cultivation using a wick system is one of the techniques used to increase the production of spinach (Amaranthus hybridus L.). One of the disadvantages of hydroponics is the occurrence of nutrient deposition, to reduce nutrient deposition in the wick system is to apply nanotechnology to break down particles in the planting medium and nutrients used, that the particles become smaller and more easily absorbed by plants, and reduce precipitation in the wick system. This research was conducted using the RAL method (Completely Randomized Design) which consisted of 6 treatments and 4 replications and namely Control (Well water + AB Mix), P1 (Nano technology water + 100% AB Mix), P2 (nano technology water + 25% POC+75% AB Mix), P3 (nano technology water+50% POC+50% AB Mix), P4 (nano technology water+75% POC+25% AB Mix), P5 (nano technology water+100% POC). The data obtained were analyzed by means of variance (ANOVA) and followed by the DMRT test at 5% level. The results of this study are that there is an effect of the use of nano technology liquid organic fertilizer on the growth of spinach which can be seen in the highest plant at P2 with 29.975 cm, the highest number of leaves is at P2 with 34 leaves, the highest leaf area is in the control with 13,71 cm2, the wet weight the highest was on P1 with 17 gr, the highest dry weight was on P2 with 1.3 gr. The use of nano technology liquid organic fertilizer has an influence on the growth of green spinach which is cultivated hydroponically.